2017
DOI: 10.3390/molecules22081270
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in the Modification of Quercetin Leading to Anticancer Agents

Abstract: The flavonoid quercetin (3,3′,4′,5,7-pentahydroxyflavone) is widely distributed in plants, foods, and beverages. This polyphenol compound exhibits varied biological actions such as antioxidant, radical-scavenging, anti-inflammatory, antibacterial, antiviral, gastroprotective, immune-modulator, and finds also application in the treatment of obesity, cardiovascular diseases and diabetes. Besides, quercetin can prevent neurological disorders and exerts protection against mitochondrial damages. Various in vitro st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(126 citation statements)
references
References 85 publications
(128 reference statements)
4
120
0
2
Order By: Relevance
“…Habtemariam et al [53] found that eriodictyol with 3 ,4 -OH showed the strongest protective effect on L-929 cells from tumor necrosis factor (TNF)-induced cell death, while hesperidin (with 3'-OH but without 4'-OH) had no protective effect. It indicated that the flavones with 3',4'-OH had strong antioxidant activity, like dihydroquercetin and quercetin (compounds 1 and 3) [54][55][56][57]. Dihydroquercetin (compound 1) as well-known antioxidants protect DNA from oxidative damage and against oxidative stress by stimulating the expression of HO-1 and NQO1 through the Nrf2-dependent antioxidant pathway [58].…”
Section: The Structural Features and The Antioxidant And Anti-prolifementioning
confidence: 99%
“…Habtemariam et al [53] found that eriodictyol with 3 ,4 -OH showed the strongest protective effect on L-929 cells from tumor necrosis factor (TNF)-induced cell death, while hesperidin (with 3'-OH but without 4'-OH) had no protective effect. It indicated that the flavones with 3',4'-OH had strong antioxidant activity, like dihydroquercetin and quercetin (compounds 1 and 3) [54][55][56][57]. Dihydroquercetin (compound 1) as well-known antioxidants protect DNA from oxidative damage and against oxidative stress by stimulating the expression of HO-1 and NQO1 through the Nrf2-dependent antioxidant pathway [58].…”
Section: The Structural Features and The Antioxidant And Anti-prolifementioning
confidence: 99%
“…Quercetin (3,5,7,3′,4′‐pentahydroxyflavone) is a polyphenolic flavonol molecule present in many fruits and vegetables such as onions, apples, berries, peanuts, soybeans, potatoes, broccoli, grapes, citrus fruits, and tea . Several reports highlighted the potential of quercetin against behavioral deficits in different animal models …”
Section: Quercetinmentioning
confidence: 99%
“…In addition, many of these compounds have common targets, suggesting that different compounds may provide synergistic effects. Quercetin belongs to the avonol group of polyphenolic compounds, which functions as antibacterial, antiviral, anti-in ammatory, antioxidant, anticancer, anti-diabetic, immunomodulatory, etc [72]. The existing studies [73][74][75]have provided convincing evidence on the renoprotective effects of quercetin in both animal and cell models of DKD.…”
Section: Discussionmentioning
confidence: 99%